DAMPAK PENGEMBANGAN PERUMAHAN TERHADAP PENINGKATAN KAWASAN RAWAN BENCANA LONGSOR LAHAN DI KOTA SEMARANG - Sutardji, - (Faculty of Social Science, Universitas Negeri Semarang, 2009)
Research conducted in District Gunungpati, aims to: identify the development of settlements,Ã‚Â knowing the level of vulnerability to land slides, and knowing the condition of the community who liveÃ‚Â in landslide-prone area.Variable data includes topography, geomorphology, geology, soil, and land use;Ã‚Â data residential development; landslide area of land; population socioeconomic data. The approach takenÃ‚Â by way of overlay maps, calculating the level of vulnerability with scoring, and quantitative descriptiveÃ‚Â analysis.The research of results showed that the function of Gunungpati district development area does notÃ‚Â meet RUTRK, where housing is built on the Kalibeng formation which is the labile region a potentiallyÃ‚Â unstable landslide occurred in the rainy season, the developer built housing in this formation are: HousingÃ‚Â in Meteseh, Bukit Regency Gombel , Perum Dewi Sartika, Trangkil Sejahtera, Purisartika Gunungpati.Ã‚Â Community who live in this area really know the risk of living in landslide areas, they ready live in theÃ‚Â house that always cracked.